Fungal characterisation of a contaminated marine environment: the case of the Port of Genoa (North-Western Italy). Issue 1 (2nd January 2018) - Greco, Giuseppe; Cecchi, Grazia; Di Piazza, Simone; Cutroneo, Laura; Capello, Marco; Zotti, Mirca
ABSTRACT: Nowadays, little information is available about how and if the contaminants may impact on the presence of marine fungi. Indeed, many environmental factors may facilitate the presence of specific fungal taxa. This paper deals with the mycodiversity of 22 stations characterised by contaminated seawaters of the Port of Genoa (North-Western Italy). Several substrates were taken into account and 319 vital strains were isolated belonging to 20 genera and 47 species. The most common genera were Aspergillus, Fusarium, Penicillium and Trichoderma. The fungal richness and mycodiversity were also evaluated and both appeared significantly high in most of these contaminated stations.